2018
DOI: 10.3322/caac.21444
|View full text |Cite
|
Sign up to set email alerts
|

Who's still smoking? Disparities in adult cigarette smoking prevalence in the United States

Abstract: The continuing high prevalence of cigarette smoking among specific subpopulations, many of them vulnerable, is one of the most pressing challenges facing the tobacco control community. These populations include individuals in lower education and/or socioeconomic groups; from certain racial/ethnic groups; in the lesbian, gay, bisexual, and transgender community; with mental illness; and in the military, particularly among those in the lowest pay grades. Although traditional tobacco control measures are having p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
247
3
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(307 citation statements)
references
References 45 publications
13
247
3
13
Order By: Relevance
“…Electronic health records should enable the identification of adults who meet tobacco exposure and other eligibility requirements, but early experience has demonstrated that they perform poorly, resulting in an additional burden when health care professionals need to interview patients to assess pack‐year history . Furthermore, as smoking has become increasingly concentrated in lower socioeconomic populations, greater barriers to access are experienced by adults who comprise the target population for lung cancer screening compared with other screening tests. Jemal and Fedewa reported that over 50% of current and former smokers who met USPSTF criteria in 2015 were uninsured or Medicaid‐insured .…”
Section: Screening For Lung Cancermentioning
confidence: 99%
“…Electronic health records should enable the identification of adults who meet tobacco exposure and other eligibility requirements, but early experience has demonstrated that they perform poorly, resulting in an additional burden when health care professionals need to interview patients to assess pack‐year history . Furthermore, as smoking has become increasingly concentrated in lower socioeconomic populations, greater barriers to access are experienced by adults who comprise the target population for lung cancer screening compared with other screening tests. Jemal and Fedewa reported that over 50% of current and former smokers who met USPSTF criteria in 2015 were uninsured or Medicaid‐insured .…”
Section: Screening For Lung Cancermentioning
confidence: 99%
“…Similarly, smoking prevalence in women declined from a peak of 35% in 1965 to 14% in 2015. However, with these declines, the profile of the American smoker has changed substantially, with disproportionately higher prevalence in vulnerable populations, including less educated and low‐income individuals . Smoking and the mortality associated with it also varies significantly by state .…”
Section: Mortality Trendsmentioning
confidence: 99%
“…(Drope et al, 2018). Within LMICs, lower income is usually associated with increased tobacco use prevalence as well, (World Health Organization, 2014) providing opportunities to further understand the complexities of tobacco use prevention and cessation in low-income groups in HICs, including the US.…”
Section: Populations and Settingsmentioning
confidence: 99%